Determinants and importance of stress hyperglycaemia in non-diabetic patients with myocardial infarction. Issue 6552 (11th October 1986) - Oswald, G A; Smith, C C; Betteridge, D J; Yudkin, J S
Abstract : Determinants of plasma glucose concentrations were studied in patients on admission to hospital with confirmed acute myocardial infarction but without previous glucose intolerance as evidenced by raised concentrations of glycosylated haemoglobin (HbAlc). Mortality in hospital increased significantly with increasing plasma concentrations of glucose in patients with both normal (p less than 0.0001, n = 311) and borderline (p less than 0.02, n = 70) concentrations of HbAlc. There was a weak relation between plasma glucose concentrations and infarct size as estimated by peak aspartate transaminase activity in both HbAlc groups (rs = 0.26, n = 101 and rs = 0.41, n = 35 respectively). A correlation was found between adrenaline and plasma glucose concentrations (r = 0.47, n = 27) and cortisol and plasma glucose concentrations (r = 0.75, n = 19), but the relation of plasma noradrenaline and plasma glucose suggested a threshold effect. Concentrations of adrenaline, but not those of noradrenaline or cortisol, correlated with infarct size as measured both by peak aspartate transaminase activity and cumulative release of creatine kinase MB isoenzyme. Multiple regression analysis showed that concentrations of cortisol, adrenaline, and noradrenaline (but not the concentration of HbAlc, infarct size, or age) are the main determinants of plasma glucose concentration measured in non-diabetic patients when admitted to hospital after acute myocardial infarction.